A rare case of severe hypertriglyceridemia induced pancreatitis in pregnancy - Kashyap, Poonam; Prasad, Sudha; Bhushan Singh, Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Acute pancreatitis is caused by various causes such as Gall stone disease, alcoholism, drug abuse but rarely caused by severe hypertriglyceridemia. It typically presents as acute or recurrent pancreatitis. The hypertriglyceridemia can be gestation induced or familial. The family history of the pregnant women needs to be taken in detail. The serum triglyceride levels in the range of 1000 to 2000 mg/dl in patients with type I, III, IV and V hyperlipoproteinemia (Friedrickson's classification) is the identifiable risk factor. The clinical course of hypertriglyceridemia induced pancreatitis is similar to other causes. We hereby report a case of 21-year-old lady G3P1L0A1 with 37 weeks of pregnancy without any family history of hypertriglyceridemia and but with history of recurrent episodes of acute pancreatitis.